Deconstructing the transmembrane core of class A G protein–coupled receptors. Issue 12 (December 2021) - Smith, Steven O.
Abstract : Class A G protein–coupled receptors have evolved to recognize ligands ranging from small-molecule odorants to proteins. Although they are among the most diverse membrane receptors in eukaryotic organisms, they possess a highly conserved core within their seven-transmembrane helix framework. The conservation of the transmembrane core has led to the idea of a common mechanism by which ligand binding is coupled to the outward rotation of helix H6, the hallmark of an active receptor. Nevertheless, there is still no consensus on the mechanism of coupling or on the roles of specific residues within the core. Recent insights from crystallography and NMR spectroscopy provide a way to decompose the core into its essential structural and functional elements that shed new light on this important region. Highlights: G protein–coupled receptors (GPCRs) have a transmembrane (TM) core that converts extracellular signals into one or more intracellular signals. Decomposition of the conserved TM core of class A GPCRs in terms of different residue types suggests that the core has three functions: to form a structural scaffold, to modulate the dynamics of the Pro6.50 hinge, and to stabilize the inactive and active conformations of helix 6 (H6). Analysis of the conserved residues in the olfactory receptors provides insights into the essential functions of the TM core in these receptors and how different class A subfamilies have evolved to accommodate their unique ligands. Understanding the function of the TM core of class A receptors provides a foundation for analyzing other GPCR classes.